PENDAMPINGAN PEMBUATAN ALAT CETAK UNTUK TEMPE DEBOG DALAM RANGKA STANDAR UKURAN DAN TEBAL TEMPE DI DESA TEGALREJO PROBOLINGGO - Koeshardjono, R. Hery; Widayanto, Mutinda Teguh; Firmansyah, Vebrian Dito; Putri, Iis Yuliyana; Prasanti, Dinda Puspita Ayu; Nily, Farida Chusnia; Sholehatun, Sholehatun (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2024)
The size and thickness of tempe debog (banana tree fronds) is not standard because when the soft soybeans are spread over the banana tree fronds there is no size depending on the density when pressing the soybeans it can lengthen or widen so that the edges of the tempe are uneven between the sides and the thickness of the tempe is uneven. The purpose of this service is to make tempe molding tools to provide a standard size and thickness of the tempe produced. The method used follows the implementation stages for activities, namely conducting field surveys, following the process of making debog tempeh, analyzing what is needed in the production process. Based on the results of the analysis of observations while at the tempe production site, it is necessary to make a tempe mold when the soybeans are spread over the fronds of banana trees so that the size and thickness of the tempe meet the standards and the density of the tempe is even. The results of the students' activities were making a printing tool made of rectangular wood for tempeh molds with standard tempeh sizes and thicknesses. Keywords : Tempe debog, Standard Size and Thickness, Tempe printing tool